Severe hailstorms near Southern Andes in the presence of mountain waves - de la Torre, Alejandro (2011)
Experimental satellite and radar data and numerical simulations at constant pressure levels were analyzed to estimate the relative importance of mountain waves during the development of 3 severe deep convection events with abundant hail precipitation in Mendoza, Argentina. The mesoscale numerical simulation model WRF 3.0 was used to determine the regional circulation previous to the deep convection. GPS radio occultation data were used to validate the simulations. It was found that updrafts generated by mountain waves constitute a possible triggering mechanism during the storms initiation. A continuous wavelet transform analysis was applied to the vertical velocity. In all cases, large amplitude stationary waves were observed just before the initiation of convection, possibly triggering it. The horizontal direction of propagation and the corresponding horizontal and vertical wavelengths of both main modes were identified. Vertical velocity and convective inhibition index were found to be potential storm forecasting flags in this region.